Rescuing apoptotic neurons in Alzheimer’s disease using wheat germ agglutinin-conjugated and cardiolipin-conjugated liposomes with encapsulated nerve growth factor and curcumin - Kuo YC (Dove Medical Press, 2015)
Yung-Chih Kuo, Ching-Chun Lin Department of Chemical Engineering, National Chung Cheng University, Chia-Yi, Taiwan, Republic of China Abstract: Liposomes with cardiolipin (CL) and wheat germ agglutinin (WGA) were developed to permeate the blood–brain barrier and treat Alzheimer’s disease. WGA-conjugated and CL-incorporated liposomes (WGA-CL-liposomes) were used to transport nerve growth factor (NGF) and curcumin (CUR) across a monolayer of human brain-microvascular endothelial cells regulated by human astrocytes and to protect SK-N-MC cells against apoptosis induced by ß-amyloid1–42 (Aß1–42) fibrils. An increase in the CL mole percentage in lipids increased the liposomal diameter, absolute zeta potential value, entrapment efficiency of NGF and CUR, release of NGF, biocompatibility, and viability of SK-N-MC cells with Aß1–42, but decreased the atomic ratio of nitrogen to phosphorus and release of CUR. In addition, an increase in the WGA concentration for grafting enhanced the liposomal diameter, atomic ratio of nitrogen to phosphorus, and permeability of NGF and CUR across the blood–brain barrier, but reduced the absolute zeta potential value and biocompatibility. WGA-CL-liposomes carrying NGF and CUR could be promising colloidal delivery carriers for future clinical application in targeting the blood–brain barrier and inhibiting neurotoxicity. Keywords: Alzheimer’s disease, nerve growth factor, curcumin, wheat germ agglutinin, cardiolipin, liposome